2007
DOI: 10.1007/s10798-007-9037-1
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative learning in technology education: D&T unit on puppetry in different Indian socio-cultural contexts

Abstract: The paper reports on the trials of a Design and Technology (D&T) unit carried out in three different Indian contexts with a focus on collaborative learning. Both collaboration and technology education are not common to the Indian school system. As part of a larger project to introduce technology education, suitable for middle school girls and boys in urban and rural areas, three culturally appropriate and gender sensitive D&T units were developed. All the units were tried out with middle school students in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…They viewed self and peer assessment, in their classes of over 40 students, to be impractical and unreliable, as students were not "mature" enough to grade "impartially." Research studies of design and technology projects among fewer middle school students from similar contexts showed that groups of students, even with different abilities, learned to work together effectively through engaging in complex projects involving multiple tasks (Khunyakari, Mehrotra, Chunawala, & Natarajan, 2007;Mehrotra, Khunyakari, Natarajan, & Chunawala, 2009). The studies also referred to impartial self and peer assessment of products by students.…”
Section: Discussionmentioning
confidence: 99%
“…They viewed self and peer assessment, in their classes of over 40 students, to be impractical and unreliable, as students were not "mature" enough to grade "impartially." Research studies of design and technology projects among fewer middle school students from similar contexts showed that groups of students, even with different abilities, learned to work together effectively through engaging in complex projects involving multiple tasks (Khunyakari, Mehrotra, Chunawala, & Natarajan, 2007;Mehrotra, Khunyakari, Natarajan, & Chunawala, 2009). The studies also referred to impartial self and peer assessment of products by students.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of D&T units offers opportunities for both individual and team productions, sharing of resources and negotiation of ideas. The nature of intra and intergroup collaborations and communications as part of students' activities in one of the D&T units has been studied and reported elsewhere (Mehrotra, Khunyakari, Natarajan, & Chunawala, 2006). The study seeks to make technology education applicable within the country's widely different socio-cultural settings.…”
Section: Discussionmentioning
confidence: 99%
“…Puppets and puppetry have the potential to help students integrate into a group and learn how to work cooperatively. In the data set, four studies (Korosec, 2012;Mehrotra, Khunyakari, Natarajan, & Chunawala, 2007;Remer & Tzuriel, 2015) highlight co-operation within and integration into a group. Korošec (2012) notes how "[s]ilent and shy children, showoffs, hyperactive and lonely children" need special support, and how direct communication with them may be unsuc-cessful, leading to rejection.…”
Section: Elementary Classroom In Usamentioning
confidence: 99%
“…Cooperation with the puppet helped them participate (Remer & Tzuriel, 2015). Mehrotra, Khunyakari, Natarajan, and Chunawala (2007) report on the trials of a Design and Technology (D&T) unit carried out in Indian middle schools in different sociocultural settings with a focus on collaborative learning. The design and technology unit includes a unit on puppetry, which involves making a puppet and staging a puppet-show.…”
Section: Elementary Classroom In Usamentioning
confidence: 99%